Attitudes and practice of surgeons in reporting medical errors at a tertiary care hospital - Zayed Rashid; Hashim Talat Khan; Fakeha Rehman; Saeed Ahmad; Shahida Niazi; Muhammad Zeeshan Sarwar (Journal of the Pakistan Medical Association, 2020)
Abstract Medical error reporting is essential in creating a culture of accountability in our healthcare system. The aim of this study was to evaluate the frequency of reporting errors by surgeons in our setup and to analyse the factors resulting in under-reporting of medical errors. A total of 96 practicing surgeons at Mayo Hospital, Lahore were surveyed between the months of February, 2018 to June 2018 on their beliefs regarding the reporting of medical errors by means of a specifically designed questionnaire. This study revealed that 71 (74%) respondents had committed a medical error but only 16 (16.6%) of them reported those errors. Major factors in under-reporting of errors included work stress and fear of medico-legal consequences due to disclosure of error. Eighty-four (87.5%) believed that increase in reporting medical errors would contribute to a better system. Continuous...